Does transient hypothyroxinemia influence metabolic bone disease of prematurity? - BEREKET, ABDULLAH; TOPUZOĞLU, AHMET; ÖZEK, EREN (TAYLOR & FRANCIS LTD, 2013)
Objective: To investigate the relationship between Metabolic Bone Disease (MBD) and Transient Hypothyroxinemia of Prematurity (THOP). Method: One hundred twenty-four infants, born in Marmara University Hospital with a gestational age <= 34 weeks, were enrolled. Clinical features were recorded. Serum TSH, free T-4, total T-4, calcium, phosphorus and total Alkaline Phosphatase (ALP) levels were determined in the first and third postnatal weeks. MBD was defined as a phosphorus level <4.5 mg/dl and/or ALP >900 IU/l. THOP was defined as a serum free and/or total thyroxine level lower than -1 SD for gestational age at the 7th postnatal day. Result: THOP was diagnosed in nineteen (15.3%) patients. MBD was diagnosed in 52 (41.9%) at the 3rd month. Low birth weight, low gestational age and prolonged parenteral nutrition were associated with MBD. Multivariate analysis documented a significant relationship solely between MBD and gestational age. Conclusion: The risk of MBD does not increase significantly in babies with THOP.
Keywords: Alkaline phosphatase; metabolic bone disease; prematurity; thyroid hormones; transient hypothyroxinemia; SERUM THYROID-HORMONES; BIRTH-WEIGHT INFANTS; DEVELOPMENTAL-TRENDS; HYPOTHYROIDISM; FRACTURES; GROWTH; CORD